Germination and dormancy of red and white rice seeds (Revista de Ciências Agroveterinárias, 2013)
White rice seeds have dormancy, but of lower intensity than red rice seeds. However some red rice genotypes have been observed with similar intensity to the dormancy of white rice seeds. After the physiological maturity stage, seeds can be exposed to less favorable conditions. Thus, the objectives were to determine the physiological maturity stage and to monitor germination and dormancy at 0, 30 and 60 days after the seed harvest of red and white rice genotypes. The experiment to determine the physiological maturity stage was a completely randomized block subdivided into plots and five replications. Data was obtained by regression analysis. Germination and dormancy data in each storage period was submitted to variance analysis, according to a completely randomized block design, analyzed as a 4 (genotypes) x 3 (1 and 2 control treatments break dormancy) factorial, with fi ve replications. Means were compared by the Student-Newman-Keuls at 5% probability level. Physiological maturity of seeds from rice genotypes Vermelho Pequeno, Vermelho Virgínia, SCSBRS Tio Taka and EPAGRI109 is reached at dent stage. A 30-day storage period is effi cient at overcoming the seed dormancy of the Vermelho Pequeno genotype but a 60-day period is required by the other genotypes.
Keywords: Oryza sativa L.; Germination; Vigor.